Selected aspects of shaping the adulthood attributes of clients in social work - Joanna Kluczyńska (Studia z Teorii Wychowania)
The article presents the elements of social work, which are important for shaping the aspects of clients' adulthood. The methods, techniques and forms of help should mobilize the client to be active and independent. In the process of help, it is important to build a mutual relationship between a social worker and a client based on the treating as a subject, showing respect and listening. Such an attitude towards the assisted person is aimed at strengthening him/her on the way to regain control over his/her own life, to build a faith in his/her own possibilities and to take responsibility for his/her own fate and the fate of people dependent on the client. The social worker participates also in the process of empowering young people, who are brought up in foster care, and in the case of children from dysfunctional families, the social worker makes sure that they are not overwhelmed by the challenges of adulthood.